Penguatan Kapasitas Kelompok Sadar Wisata (Pokdarwis) Tentang Tourism Branding di Desa Baro Kecamatan Setia Bakti Kabupaten Aceh Jaya - Ilham Mirza Saputra; Vellayati Hajad; Ikhwan Rahmatika Latif; Ikhsan Ikhsan; Deni Setiawan (Universitas Teuku Umar, 2023)
Baro Village, Setia Bakti District, Aceh Jaya Regency has eco-tourism potential for mangrove forests, which actually play a role in reducing unemployment and poverty and aiming to be environmentally friendly. However, a fundamental problem in almost all nature-based tourism in the region is related to the absence of a brand destination. As a result, tourist destinations are empty of visitors, which ultimately affects Pokdarwis' income as a manager of mangrove tourism. The method of implementing community service is through Participatory Action Research (PAR), which is participatory-based and emphasizes the process of sharing and learning together so that it can help Dikti personnel understand the conditions and problems of partners, namely Baro Village, Setia Bakti District, Aceh Jaya Regency in the use of media. This service was ultimately able to encourage the use of social media for the Baro Village Pokdarwis through increasing the Pokdarwis' ability to create digital content in the form of websites, videos, and posters of digital tourism products; the formation of SOPs for branding mangrove forest tourism destinations; preparing a schedule for digital mangrove forest competitions and festivals, and establishing networking and collaboration with the government, private sector, and digital media actors.